1 - Democracy and Development – A Disputed Pair - Rudebeck, Lars (Africa Development, 2021)
The text moves in the historical context of decolonization, post-colonialism, globalization and ‘developing countries’. In this context, the two terms ‘development’ and ‘democracy’ are used all over, in everyday language as well as in public and theoretical discourse, not least in relation to Africa. What different meanings do these terms convey? The various concepts referred to by them are often seen as linked to each other. How may such linkages be conceived? These are questions raised in this article. Conceivable answers are presented and analyzed. Emphasis is on concepts existing today and their actual use in grasping or even shaping current realities. The level of the analysis is abstract. But its empirical foundations are very concretely close to the ground, shaped since the 1960s through long periods of fieldwork in Tunisia, Guinea-Bissau and Mozambique. Concrete references, thus, are primarily to links between politics and people’s efforts in post-colonial Africa to achieve ‘development’, while theoretical inferences are global. The overall answer emerging from the text is that development, including sustainable development, meeting legitimate majority needs and aspirations is more likely to take place under conditions of substantial democracy than under other forms of rule. The equalization of political power through democratic self-empowerment is crucial. Democracy and development are indeed related to each other – but not just any democracy and not just any development, nor all of the time.